2020
DOI: 10.1089/dna.2020.5775
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pomegranate Extract in Mesenchymal Stem Cells by Modulation of microRNA-155, microRNA-21, microRNA-23b, microRNA-126a, and PI3K\AKT1\NF-κB Expression

Abstract: Today, mesenchymal stem cells (MSCs) are candidates for various autoimmune disease treatments due to immunomodulatory activity in these cells. Much research has recently been done to improve the immunomodulatory activity of MSCs. Genetic variation is one of these methods. microRNAs (miRNAs) are small noncoding RNAs that control most of the cell's biological activities. Recent studies have shown that miRNAs play a significant role in the regulation of MSC immunomodulatory activity. Pomegranate is a fruit that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
2
5
0
Order By: Relevance
“…In fact, it has already been proven that these pathways are the target genes of four miRs and are linked to the immunomodulatory properties of MSCs. 47 Similar to our findings, consistently, curcumin reduces nuclear factor-kappa B (NF-κB) and inhibits the phosphorylation of AKT via phosphatidylinositol-3-kinase (PI3K), which reduces the level of proinflammatory cytokines, chemokines and adhesion molecules. [37][38][39] On the other hand, these pathways are involved in the immunoregulatory activity of hDPSCs and PC can be highly effective in this regard.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In fact, it has already been proven that these pathways are the target genes of four miRs and are linked to the immunomodulatory properties of MSCs. 47 Similar to our findings, consistently, curcumin reduces nuclear factor-kappa B (NF-κB) and inhibits the phosphorylation of AKT via phosphatidylinositol-3-kinase (PI3K), which reduces the level of proinflammatory cytokines, chemokines and adhesion molecules. [37][38][39] On the other hand, these pathways are involved in the immunoregulatory activity of hDPSCs and PC can be highly effective in this regard.…”
Section: Discussionsupporting
confidence: 85%
“…Procedures for the integrated analyses of miRNAs and target genes have been previously reported. 47 The three steps were: miRNA target prediction using the TargetScan algorithm, data compilation for identi-…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, in vitro and in vivo studies have revealed that a pomegranate extract reduces miR-155 expression while it induces expression of SHIP-1, inhibition of pAkt, and expression of pPI3K [ 152 ]. In fact, miR-155 downregulation plays an important role in pathways of immune modulation in adipose-derived mesenchymal stem cells treated with a pomegranate extract (Ad-MSCs) [ 153 ]. On the other hand, genistein inhibits breast cancer cell proliferation and down-regulates miR-155 expression thereby inducing caspase-mediated cell death [ 154 ].…”
Section: Mir-155 In Carcinogenesis and Mirna-based Monitoring Of Disease Progressionmentioning
confidence: 99%